Expectations of People in Bangkok Regarding to Using Drone for Goods Delivery - Charoensook, Chartchai; Jirathammawat, Natthawut; Yuenchon, Bordin; Ratanabutchai, Vilasinee; Monthong, Sunutthorn (Journal of Buddhist Education and Research (JBER), 2025)
In the rapidly evolving digital era, the utilization of drones or unmanned aerial vehicles (UAVs) for goods transportation has gained increasing prominence across numerous nations, including Thailand. Particularly within large urban centers like Bangkok, this concept has emerged as a compelling area of interest and extensive research. This study aims to: 1) Investigate the factors influencing the expectations of residents in metropolitan Bangkok regarding the adoption of drones for goods delivery, and 2) Compare the expectations of the public towards drone-based goods delivery, categorized by personal factors. Employing a survey research design, data on expectations were collected from a sample of 400 residents residing in Bangkok using questionnaires. The collected data were analyzed using descriptive and inferential statistics. The findings revealed that personal factors significantly influence the variation in expectations. Furthermore, the majority of the public holds high expectations regarding the benefits of drone-based goods delivery, especially concerning the reduction of environmental impact associated with traditional transportation methods. The conclusions drawn from this research provide crucial insights for developing efficient drone-based goods delivery service models that effectively address consumer needs, enabling access to and the practical application of advanced technologies for tangible benefits.